PTH-076 Severity of bile acid malabsorption correlates with length of ileal resection in crohn's disease. (17th June 2017) - Skouras, T; Prasad, Y; Dodd, S; Subramanian, S
Abstract : Introduction: Bile acid malabsorption (BAM) is a common cause of diarrhoea in Crohn's disease (CD) patients with ileal resection and can lead to complications such as renal and biliary stone disease. BAM is usually diagnosed by selenium labelled homo-taurocholic acid test ( 75 SeHCAT) but its availability is limited. Thus, a large proportion of resected CD patients either remain underdiagnosed or subject to empirical therapy. There is a paucity of studies examining the correlation between length of ileal resection and severity of BAM which will be of particular use to clinicians with no recourse to diagnostic testing for BAM. Method: We identified all CD patients with a prior surgical resection who underwent 75 SeHCAT testing at our institute. Testing was based on the treating clinician's discretion. The length of resected ileum was recorded from histopathology report. We conducted a Spearman's correlation test to check for correlation between length of resected ileum and percentage retention on 75 SeHCAT. Response to treatment with bile salt sequestrant and 75 SeHCAT retention values was tested using Mann-Whitney test. Results: A total of 97 patients were identified with a mean age of 46.4 (SD 14.5). The median length of resected ileum was 22.5 cms (range 1.5–95 cms) with a median of 1 resection (range 1–4). Overall, 90 patients (92.8%) had 75 SeHCAT retention values of <5%, 5 (5.2%) patients between 5%–10% and only 2 patients had values of >15%. There was moderate correlation between 75 SeHCAT retention and length of ileal resection (Spearman's rho: 0.4041, p<0.001). Data on response to treatment was available for 60 patients, of who 41 (42%) responded and 19 (19%) failed to respond to bile salt sequestrants. The 75 SeHCAT retention values was comparable among responders (median 0.02%, range 0.1–6.6) and non-responders (median 0.02%, range 0.1–6.6, Mann-Whitney test, p=0.72). Conclusion: There was moderate correlation between length of ileal resection and severity of BAM as defined by 75 SeHCAT retention values. Response to bile salt sequestrant therapy was not dependent on 75 SeHCAT retention values. Disclosure of Interest: None Declared